2004
DOI: 10.1111/j.0021-8901.2004.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exotic trout on native charr in a Japanese stream

Abstract: Summary1. Regression and isodar methods developed by community ecologists provide tools for evaluating the existence and magnitude of interspecific interactions in the field. In this study, we examined the usefulness of both methods to assess the impact of exotic trout on native charr. 2. Brown trout Salmo trutta and rainbow trout Oncorhynchus mykiss have been introduced world-wide. They are invading many streams in Japan that also harbour native salmonids. We studied these species and the endemic Asian white-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 56 publications
1
55
0
Order By: Relevance
“…The rainbow trout could have altered mountain catfish habitat associations and abundances through direct predation, as reported from previous studies (Butler & Marshall, 1996;Marriott et al, 1997;. Because deeper habitats provide refugia and optimal feeding habitats for trout (McIntosh, 2000;Morita et al, 2004;, particularly the larger-sized individuals (pers. obs), predation pressure on the mountain catfish is likely to be highest in the deeper pools.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The rainbow trout could have altered mountain catfish habitat associations and abundances through direct predation, as reported from previous studies (Butler & Marshall, 1996;Marriott et al, 1997;. Because deeper habitats provide refugia and optimal feeding habitats for trout (McIntosh, 2000;Morita et al, 2004;, particularly the larger-sized individuals (pers. obs), predation pressure on the mountain catfish is likely to be highest in the deeper pools.…”
Section: Discussionmentioning
confidence: 75%
“…It is likely, however, that the mountain catfish with trout-invaded reaches may occupy sub-optimal habitat, which may influence their foraging, recruiting, and reproductive success (Ngugi et al 2009). Cases where native taxa have been forced to occupy marginal or sub-optimal habitats have been documented in other studies for native fishes (Morita et al, 2004;Ngugi et al, 2009) and amphibians (Bosch et al, 2006). These marginal habitats may, however, be less optimal and could further expose the catfish to terrestrial predators such as otters and predatory birds, and therefore may not be suitable for long-term sustenance of large catfish populations.…”
Section: Trichopteramentioning
confidence: 98%
“…Parr densities were estimated in a 100 m reach of each site using the three-pass removal method (model M (b) , program CAPTURE, available at http://www.mbr-pwrc.usgs.gov/software/index.html). At the same time, four physical characteristics (river width, depth, velocity and substrate code) were measured in each 100 m reach of each site following Morita et al (2004). Water temperatures were measured at each site at hourly intervals using data loggers ( A PMRN method based on logistic regression (Heino et al 2002) was used to analyse the relationships between body size and the probability of becoming mature for age 1þ year male parr.…”
Section: Methodsmentioning
confidence: 99%
“…Invaders can directly influence native population dynamics, abundance and persistence through biological interactions such as competition, predation and/or parasitism (e.g. Blackburn et al 2004, Morita et al 2004, Gozlan et al 2005, Ortega et al 2006. Numerous studies have also revealed the ecological effects of invaders on native species at higher levels of organization, such as at the community and/or the ecosystem level (e.g.…”
Section: Introductionmentioning
confidence: 99%